Kapabilitas Teknologi Informasi dan Komunikasi Sekretariat Jendral DPR RI Menuju Parlemen Modern - Indra Iskandar (Inovasi, 2020)
ABSTRACT The Organization of the Secretariat General of the House of Representatives of the Republic of Indonesia (Setjen DPRRI) has an important role as a support system for the implementation of the duties and functions of the DPRRI. Public distrust of parliaments and public understanding of democratic political systems can result in political instability. With the existence of a modern DPPRI, it is hoped that public trust in parliament will return. The purpose of this study is to analyze the capability of the DPRRI secretariat general information technology in support of the modern DPRRI. The research methodology used is descriptive method. Data collection techniques used were direct observation, in-depth interviews with related parties, distribution of questionnaires to 82 employees of the General Secretariat of the Republic of Indonesia echelon 1 to 3. This research was conducted at the Secretariat General of the DPRRI during December 2019 until January 2020. The results showed the capability of Technology and Information (TKI) of the DPPRI secretary general is good with applications built for the needs of internal employees, board members and the general public. This good ICT has not been used maximally either by the secretary general's staff, members of the DPRRI and the general public due to lack of socialization and the ability of its users. So it is recommended massive socialization and training so that existing ICT infrastructure can be fully utilized. This ICT capability will make modern DPRRI meaning more open, transparent and accountable, encourage people to be more involved in public life by providing quality information and greater access to DPRRI documents and activities or legislative bodies so that citizens participate in the process of making policy and legislation. This ICT capability also makes employees or the general secretary reliable as a support system for DPRRI activities and public trust in the DPRRI is increasing. Keywords: Capability; Information Communication Technology, DPRRI Modern